Comparison of Z-Source EZ-Source and TZ-Source Inverter Systems for Wind Energy Conversion - S. Bala Kumar; Samuel Kefale; Azath M (Institute of Advanced Engineering and Science, 2018)
In this paper, three different impedance source inverters: Z-source inverter, EZ- source inverter, TZ-Source for wind energy conversion system (WECS) were investigated. Total output power and THD of each of these systems are calculated. The proposed system can boost the output voltage effectively when the low output voltage of the generator is available at low wind speed. This system has higher performance, less components, increased efficiency and reduced cost. These features make the proposed TZSI based system suitable for the wind conversion systems. MATLAB simulink model for wind generator system is developed and simulation studies are successfully performed. The simulation is done using MATLAB and the simulation results are presented. This comparison shows that the TZ-source inverter is very promising for wind energy conversion system.